Experimental renal transplantation in rats improves cardiac dysfunction caused by chronic kidney disease while LVH persists - Hagmayer, Linda; Mayer, Christina; Ebert, Nadja; Amann, Kerstin; Daniel, Christoph (Frontiers in Cardiovascular Medicine, 2023)
Background: Chronic kidney disease (CKD) causes congestive heart failure (CHF) with systolic dysfunction and left ventricular hypertrophy (LVH), which is a major contributor to increased mortality in CKD patients. It remains unclear whether cardiovascular changes that occur during the course of CKD can be reversed when renal function is restored by transplantation. Methods: To investigate this, chronic kidney disease was established in F344 rats by subtotal nephrectomy (SNx) for 8 weeks, followed by transplantation of a functional kidney from an isogenic F344 donor. SNx rats without transplantation and sham-operated animals served as controls. Renal function was assessed before and throughout the experiment. In addition, cardiac ultrasound was performed at weeks 0, 8, 12 and 16. At the end of the experiment, intra-arterial blood pressure was measured and kidneys and hearts were histologically and molecularly examined. Results: Eight weeks after SNx, rats developed marked renal dysfunction associated with significant glomerulosclerosis and tubulointerstitial fibrosis, but also an increase in left ventricular mass. After transplantation, renal function normalized but relative heart weight and ventricular mass as assessed by ultrasound scans showed no reduction compared with SNx controls. However, left ventricular wall thickness, fractional shortening and ejection fraction was normalized by renal transplantation. At 8 weeks after kidney transplantation, cardiac expression of BNP and FGF23 was also at levels comparable to healthy controls, whereas these factors were significantly increased in SNx rats. Cardiac fibrosis, as measured by fibronectin mRNA expression, was completely normalized, whereas cardiac fibronectin protein was still slightly but not significantly increased in transplanted animals compared to controls. In addition, the myofibroblast marker collagen 1, as assessed by immunohistochemistry, was significantly increased in SNx rats and also normalized by renal transplantation. Interestingly, CD68+ macrophages were significantly reduced in the hearts of SNx rats and in transplanted animals at slightly higher levels compared to controls. Conclusion: Restoration of renal function by kidney transplantation normalized early cardiac changes at most functional and molecular levels, but did not completely reverse LVH. However, further studies are needed to determine whether restoration of renal function can also reverse LVH at a later time point.